From Mimicry to Language: A Neuroanatomically Based Evolutionary Model of the Emergence of Vocal Language - Poliva, Oren (Frontiers in Neuroscience, 2016)
The auditory cortex communicates with the frontal lobe via the middle temporal gyrus (auditory ventral stream; AVS) or the inferior parietal lobule (auditory dorsal stream; ADS). Whereas the AVS is ascribed only with sound recognition, the ADS is ascribed with sound localization, voice detection, prosodic perception/production, lip-speech integration, phoneme discrimination, articulation, repetition, phonological long-term memory and working memory. Previously, I interpreted the juxtaposition of sound localization, voice detection, audio-visual integration and prosodic analysis, as evidence that the behavioral precursor to human speech is the exchange of contact calls in non-human primates. Herein, I interpret the remaining ADS functions as evidence of additional stages in language evolution. According to this model, the role of the ADS in vocal control enabled early Homo (Hominans) to name objects using monosyllabic calls, and allowed children to learn their parents’ calls by imitating their lip movements. Initially, the calls were forgotten quickly but gradually were remembered for longer periods. Once the representations of the calls became permanent, mimicry was limited to infancy, and older individuals encoded in the ADS a lexicon for the names of objects (phonological lexicon). Consequently, sound recognition in the AVS was sufficient for activating the phonological representations in the ADS and mimicry became independent of lip-reading. Later, by developing inhibitory connections between acoustic-syllabic representations in the AVS and phonological representations of subsequent syllables in the ADS, Hominans became capable of concatenating the monosyllabic calls for repeating polysyllabic words (i.e., developed working memory). Finally, due to strengthening of connections between phonological representations in the ADS, Hominans became capable of encoding several syllables as a single representation (chunking). Consequently, Hominans began vocalizing and mimicking/rehearsing lists of words (sentences).